1997
DOI: 10.1046/j.1365-3083.1997.d01-434.x
|View full text |Cite
|
Sign up to set email alerts
|

MHC Class I Presentation of Live and Heat‐Inactivated Sendai Virus Antigen in T2Kb Cells Depends on an Intracellular Compartment with Endosomal Characteristics

Abstract: T2K b cells, which do not express TAP1/2 peptide transporters or the low molecular weight protein 2/7 (LMP2/ 7) proteasomal subunits, can still process and present both live and heat-inactivated Sendai virus (SV). As this operation may also reflect the existence of an alternative processing pathway in normal antigen-presenting cells (APC), the authors have characterized it using intracelluular inhibitors and anti-K b monoclonal antibodies (MoAbs). From the results with lipophilic amines (ammonium chloride, met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Necrotic ovarian tumor cells were induced by incubating the ovarian tumor cells in a hypotonic solution for 30 min at 37°C and cell death was determined by uptake of Trypan blue solution. The DCs were pretreated with BFA as described in Material and Methods 54. DCs + apoptotic cell, DCs cocultured with apoptotic autologous ovarian tumor cells for 24 hr as stimulators; DCs + tumor cells, DCs cocultured with untreated live ovarian tumor cells for 48 hr as stimulator; DCs + necrotic cells, DCs cocultured with necrotic ovarian tumor cells for 24 hr.…”
Section: Resultsmentioning
confidence: 99%
“…Necrotic ovarian tumor cells were induced by incubating the ovarian tumor cells in a hypotonic solution for 30 min at 37°C and cell death was determined by uptake of Trypan blue solution. The DCs were pretreated with BFA as described in Material and Methods 54. DCs + apoptotic cell, DCs cocultured with apoptotic autologous ovarian tumor cells for 24 hr as stimulators; DCs + tumor cells, DCs cocultured with untreated live ovarian tumor cells for 48 hr as stimulator; DCs + necrotic cells, DCs cocultured with necrotic ovarian tumor cells for 24 hr.…”
Section: Resultsmentioning
confidence: 99%
“…First, exogenous applied peptide derivates often used as substrate-based inhibitors reach pPC-containing cell compartments (31). Second, T2 cells and T2 transfectants are able to process and present exogenous peptide substrates from fluid phase by MHC I (32, 33) through a cellular pathway that is apparently independent of TAP, but requires vesicular transport between secretory compartments (34), indicating that such Ag substrates could serve in T2 cell lines as a source for an alternate MHC I presentation pathway independent of cytosol and peptide transporter (35)(36)(37). Most interestingly, studies on TAP-negative APCs suggested that processing of exogenous peptides for presentation by MHC I involves post-Golgi peptide exchange (38).…”
Section: Pc7 Mediates the Liberation Of Epitopes From Exogenous Peptimentioning
confidence: 99%
“…Exogenous Ag can be processed via alternate MHC-I Ag-processing mechanisms, which may involve delivery of exogenous Ag from vacuolar compartments to the cytosol for cytosolic processing (8 -10) or processing wholly within vacuolar compartments without access to the cytosol (i.e., vacuolar alternate MHC-I Ag processing) (11)(12)(13)(14)(15)(16)(17). Particulate Ags, including bacteria, are efficiently processed by macrophages and dendritic cells for MHC-I presentation.…”
mentioning
confidence: 99%